2011
DOI: 10.1016/j.jcrs.2010.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laser in situ keratomileusis flaps created by 3 femtosecond lasers and a microkeratome

Hyunseok Ahn,
Jin-Kook Kim,
Chang Kook Kim
et al.

Abstract: Flap morphology differed according to the system used. The 3 femtosecond laser systems appeared to be superior to the microkeratome system generally. The 3 femtosecond laser systems also produced different flap configurations depending on their individual mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 43 publications
2
55
0
Order By: Relevance
“…Compared with a femtosecond procedure, predicting the change in rigidity when the flap is created using a mechanical microkeratome is compounded by factors such as the variability in the flap thickness profile where the meniscus of the flap is much thicker in the periphery than in the center (especially with the rotatory microkeratomes as used in this investigation), variable hinge length, shallow angled side cut and decreased flap re-adherence to the underlying stromal bed. [48][49][50]. Our data on correlation between IOP and CCT shown in Figure 3 revealed no significant change in this correlation resulting from the refractive enhancement procedure.…”
Section: Discussionmentioning
confidence: 65%
“…Compared with a femtosecond procedure, predicting the change in rigidity when the flap is created using a mechanical microkeratome is compounded by factors such as the variability in the flap thickness profile where the meniscus of the flap is much thicker in the periphery than in the center (especially with the rotatory microkeratomes as used in this investigation), variable hinge length, shallow angled side cut and decreased flap re-adherence to the underlying stromal bed. [48][49][50]. Our data on correlation between IOP and CCT shown in Figure 3 revealed no significant change in this correlation resulting from the refractive enhancement procedure.…”
Section: Discussionmentioning
confidence: 65%
“…In a recent study that evaluated the thickness and side-cut angle of LASIK flaps using Fourier-domain optical coherence tomography (OCT), flap creation for bilateral LASIK was performed using an IntraLase, VisuMax, or Femto LDV femtosecond laser or a microkeratome. The study found that flap morphology differed according to the system used and the 3 femtosecond laser systems appeared to be superior to the microkeratome system (Ahn et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…The microkeratome coupled to the artificial chamber can produce an endothelial donor lamella (EDL); however, the cutting irregularities and the unpredictability of the depth of the cut are major impediments to the visual outcome of lamellar transplantation (3,4) . New models of femtosecond lasers (FS) produce a better corneal lamella quality than the microkeratome (5)(6)(7)(8)(9) . Lasers with a high frequen cy and low energy tend to make a corneal cut smoother, more homogeneous, accurate, and reproducible, as smaller intrastromal bubbles are produced, creating smaller cavities in the cornea (5)(6)(7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%
“…New models of femtosecond lasers (FS) produce a better corneal lamella quality than the microkeratome (5)(6)(7)(8)(9) . Lasers with a high frequen cy and low energy tend to make a corneal cut smoother, more homogeneous, accurate, and reproducible, as smaller intrastromal bubbles are produced, creating smaller cavities in the cornea (5)(6)(7)(8)(9) . Cell necrosis and inflammation in the cornea increase as the energy used by FS increases (5)(6)(7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation